Murine Susceptibility to Leishmania amazonensis Infection Is Influenced by Arginase-1 and Macrophages at the Lesion Site - Tomiotto-Pellissier, Fernanda; Miranda-Sapla, Milena Menegazzo; Silva, Taylon Felipe; Bortoleti, Bruna Taciane da Silva; Gonçalves, Manoela Daiele; Concato, Virginia Márcia; Rodrigues, Ana Carolina Jacob; Detoni, Mariana Barbosa; Staurengo-Ferrari, Larissa; Verri, Waldiceu Aparecido; Costa, Idessania Nazareth; Panis, Carolina; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Cutaneous leishmaniasis is a zoonotic infectious disease broadly distributed worldwide, causing a range of diseases with clinical outcomes ranging from self-healing infections to chronic disfiguring disease. The effective immune response to this infection is yet to be more comprehensively understood and is fundamental for developing drugs and vaccines. Thus, we used experimental models of susceptibility (BALB/c) and partial resistance (C57BL/6) to Leishmania amazonensis infection to investigate the local profile of mediators involved in the development of cutaneous leishmaniasis. We found worse disease outcome in BALB/c mice than in C57BL/6 mice, with almost 15 times higher parasitic load, ulcerated lesion formation, and higher levels of IL-6 in infected paws. In contrast, C57BL/6 presented higher levels of IFN-γ and superoxide anion (•O2−) after 11 weeks of infection and no lesion ulcerations. A peak of local macrophages appeared after 24 h of infection in both of the studied mice strains, followed by another increase after 240 h, detected only in C57BL/6 mice. Regarding M1 and M2 macrophage phenotype markers [iNOS, MHC-II, CD206, and arginase-1 (Arg-1)], we found a pronounced increase in Arg-1 levels in BALB/c after 11 weeks of infection, whereas C57BL/6 showed an initial predomination of markers from both profiles, followed by an M2 predominance, coinciding with the second peak of macrophage infiltration, 240 h after the infection. Greater deposition of type III collagen and lesion resolution was also observed in C57BL/6 mice. The adoptive transfer of macrophages from C57BL/6 to infected BALB/c at the 11th week showed a reduction in both edema and the number of parasites at the lesion site, in addition to lower levels of Arg-1. Thus, C57BL/6 mice have a more effective response against L. amazonensis, based on a balance between inflammation and tissue repair, while BALB/c mice have an excessive Arg-1 production at late infection. The worst evolution seems to be influenced by recruitment of Arg-1 related macrophages, since the adoptive transfer of macrophages from C57BL/6 mice to BALB/c resulted in better outcomes, with lower levels of Arg-1.